Impact on Bacterial Resistance of Therapeutically Nonequivalent Generics: The Case of Piperacillin-Tazobactam (2016)
ABSTRACT: Previous studies have demonstrated that pharmaceutical equivalence and pharmacokinetic equivalence of generic antibiotics are necessary but not sufficient conditions to guarantee therapeutic equivalence (better called pharmacodynamic equivalence). In addition, there is scientific evidence suggesting a direct link between pharmacodynamic nonequivalence of generic vancomycin and promotion of resistance in Staphylococcus aureus. To find out if even subtle deviations from the expected pharmacodynamic behavior with respect to the innovator could favor resistance, we studied a generic product of piperacillin-tazobactam characterized by pharmaceutical and pharmacokinetic equivalence but a faulty fit of Hill’s Emax sigmoid model that could be interpreted as pharmacodynamic nonequivalence. We determined the impact in vivo of this generic product on the resistance of a mixed Escherichia coli population composed of *99% susceptible cells (ATCC 35218 strain) and a *1% isogenic resistant subpopulation that overproduces TEM-1 β-lactamase. After only 24 hours of treatment in the neutropenic murine thigh infection model, the generic amplified the resistant subpopulation up to 20-times compared with the innovator, following an inverted-U doseresponse relationship. These findings highlight the critical role of therapeutic nonequivalence of generic antibiotics as a key factor contributing to the global problem of bacterial resistance.